Antimicrobial agents in the disinfection of molds obtained in dental practice: a literature review (Research, Society and Development, 2020)
Objective: To assess which disinfecting agent has the most appropriate characteristics, as well as the best disinfection method. Method: a descriptive and exploratory literature review was carried out, seeking the most relevant studies on the agents and methods of disinfecting molds obtained in dental practice, published between 2010 and 2020, in Portuguese and English. Results: According to the reviewed literature, it is important to note that professionals are already becoming increasingly aware of the risk of cross-contamination of materials in dental practice. Therefore, in the search for an ideal disinfectant method and solution, one must consider the interaction of microbicidal properties together with the effect on the molds and models obtained, as these will serve as the basis for the construction of the dental prosthesis. It is up to the dental professional to differentiate the specific characteristics of the disinfectant solution and the technique used, as well as the interaction of both, in order to obtain the desired result. Conclusion: Based on this literature review, it was possible to conclude that there is still no ideal disinfectant solution. The most used disinfection techniques are immersion, spraying and spraying, and all the techniques showed satisfactory results.